Aplikasi penggunaan Mono Di-Acyl Glycerol (MDAG) untuk meningkatkan stabilitas dan titik leleh dark chocolate [Application of Mono Di-Acyl Glycerol (MDAG) to Improve Stability and Melting Point of Dark Chocolate] - Mursalin Mursalin; Achmad Hizazi; Sahrial Sahrial (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Chocolate is one of the processed cocoa products in the form of a water-in-oil (w/o) emulsion. In its production, cocoa powder, sugar, and vanilla are evenly dispersed in cocoa butter by using lecithin as an emulsifier. Lecithin is an effective emulsifier used to w/o emulsions due to its HLB ranging (4-6). So far, by using a single emulsifier (lecithin), it will takes 8-12 hours of conching to produce dark chocolate with good quality and stability. Hence, the addition of MDAG which has an HLB ranging 3-5 as a co-emulsifier, is expected to reduce conching time and increase product stability and melting point. The study was aimed to determine the effect of adding MDAG as a co-emulsifier to increase the stability and melting point of dark chocolate and to determine the optimum concentration of MDAG addition. The study was arranged in a completely randomized design (CRD), the treatments were 6 levels of lecithin/MDAG ratio (%) in the dough, namely P0 (0.60:0), P1 (0.56:0.04), P2 (0.52 :0.08), P3 (0.48:0.12), P4 (0.44:0.16), and P5 (0.40:0.20). Each treatment level was repeated 3 times to obtain 18 experimental units. The parameters tested were melting point and fat-blooming. To see whether there was an effect of adding MDAG as a co-emulsifier, the data obtained were analyzed using ANOVA and followed by DNMRT at a 5% significance level. The results showed that the addition of MDAG as a co-emulsifier could increase the stability and melting point of dark chocolate. The best proportion of emulsifier mixture of lecithin and MDAG is the use of 0.44% lecithin and 0.16% MDAG which produces a melting point of 34oCwith a level of stability during storage at room temperature was quite high (not having fat-bloomduring storage up to 21 days).